PENGARUH SUSTAINABILITY PERFORMANCE, CORPORATE GOVERNANCE, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN YANG DI MODERASI OLEH UKURAN PERUSAHAAN PADA SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2024 - Reginata Saharany Kustanti; Ida Bagus Ketut Bayangkara (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
ESG integration is crucial for mining company valuation in emerging markets. This study analyzes the effect of sustainability performance, corporate governance, and leverage on firm value, with firm size as moderating variable. Using SEM-PLS on 85 observations from 17 Indonesian mining companies (2020-2024), results show sustainability performance and corporate governance significantly increase firm value, while leverage significantly decreases it. Firm size shows no direct effect or moderating role, indicating uniform benefits across company scales. Findings suggest mining firms should enhance sustainability disclosure per GRI standards, strengthen governance, and maintain conservative capital structure to optimize market value.